Controversies in the atrial fibrillation сatheter ablations - А. Doronin; М. Meshkova; Y. Marushko (Ukrainian Journal of Cardiovascular Surgery, 2016)
For now there is no single technique of radiofrequency (RF) catheter ablation of atrial fibrillation (AF). We decided to analyze the main methodics of AF radiofrequency catheter ablation currently used.We analyzed the literature data and our own results.Many authors have recognized that in paroxysmal AF electrical isolation of the pulmonary veins is enough, but in non-paroxysmal AF we need to use a step by step methodology: in addition to PV isolation performing atrial fragmentation and modification of the arrhythmia substrate. However, there were studies that show advisability of the step by step procedure in paroxysmal AF, and inefficacy when it was used in patients with non-paroxysmal AF. Despite significant progress in the medical equipment and experience accumulation, efficiency of the catheter treatment of AF is not improved. It is considered that the risk of complications reducing when using of the irrigated catheters, but in 430 consecutive patients, who received AF catheter ablation in our center, we had no complications that could be associated with the use of non-irrigated catheters.There are many unresolved issues in the AF radiofrequency catheter treatment. The ablation technique that we applied is quite effective, safe and economically feasible.